Outcome of Open Reduction and Internal Fixation of Gartland III Supracondylar Fractures of The Humerus in Children Using Crossed K Wires Via Medial Incision (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To assess the Radiological & Functional outcome of open reduction and internal fixation with crossed K Wires in Gartland III displaced Fractures Supracondylar humerus in children using medial approach.Method: It was a prospective study conducted on 95 patients with displaced supracondylar fractures of the humerus Gartland III in children. All patients were managed with open reduction and internal fixation using crossed K Wires via medial approach.The most common mechanism of trauma was fall while playing; fall from height and road traffic accident. The mean follow-up time was six months and results were assessed according to Flynn’s criteria.Results: Total 95 patients with closed supracondylar fractures of the humerus Gartland III were included in this study. Male to female ratio was 56:39 (59 %:41 %). 50 (52.6 %) patients got trauma to their right elbow while left elbow was involved in 45 (47.4 %) of cases. The mean age of the patients was 7.5+2.08 years. 60 (63.15%) patients gained excellent results according to Flynn’s criteria while 17 (17.90%) patients had good and 13 (13.69%) patients achieved satisfactory results. Only 5 (5.26%) patients had poor results. The main cause of poor results was late presentation and initial quack management. No case of neurovascular injury and cubitus varus deformity was reported. All patients were happy with their scar appearance.Conclusion: Management of displaced supracondylar fractures of the humerus in children with Open reduction and internal fixation using medial incision is simple, safe and straightforward, providing more anatomical reduction and functional outcome with good scar cosmoses.